2020
DOI: 10.1016/j.copsyc.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis based modified unified theory of acceptance and use of technology (meta-UTAUT): a review of emerging literature

Abstract: Over the last more than four decades, several theoretical models have been developed to understand the acceptance and use of information systems. Realising the dilemma in selecting the appropriate theoretical model to assess the acceptance and use of technology and considering the pattern of using the Unified Theory of Acceptance and Use of Technology (UTAUT), a modified version (meta-UTAUT) has been developed based on the synthesis of results from 162 existing studies. The aim of this article is to review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 45 publications
8
126
5
4
Order By: Relevance
“…This study therefore proposes a behavioral model that explains the acceptance of mobile payments, whereby the user can perform a transaction in an agile and secure way. To develop such a model, various theories of the adoption of new technologies have been used as a basis, such as TAM [10,59], the unified theory of acceptance and use of technology (UTAUT) [24,60], and their variants, with the addition of other concepts considered important for the study of this type of technology, such as mobile user skillfulness, personal innovation, convenience and perceived risk.…”
Section: Discussionmentioning
confidence: 99%
“…This study therefore proposes a behavioral model that explains the acceptance of mobile payments, whereby the user can perform a transaction in an agile and secure way. To develop such a model, various theories of the adoption of new technologies have been used as a basis, such as TAM [10,59], the unified theory of acceptance and use of technology (UTAUT) [24,60], and their variants, with the addition of other concepts considered important for the study of this type of technology, such as mobile user skillfulness, personal innovation, convenience and perceived risk.…”
Section: Discussionmentioning
confidence: 99%
“…Intention to use is a key factor in seeing the understanding of technology users [25]. Many models have been studied, researched and developed to explain the use of technology such as: theory of reasoned action model, theory of planned behavior model, technology acceptance model and unified theory of acceptance and use of technology [26].…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…A number of models have been used to predict factors associated with the behavioral intention of m-Health [23][24][25][26][27]. Recently, UTAUT is considered as the most valid technology acceptance model used to assess behavioral intention and actual use behavior of m-Health [28][29][30][31][32]. Previous studies have shown that users' behavioral intention of information technology is the basic premise of users' use behavior [33,34].…”
Section: Introductionmentioning
confidence: 99%